2013
DOI: 10.3390/md11093324
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low-Dose Marine n-3 Fatty Acids on Plasma Levels of sCD36 in Overweight Subjects: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: CD36 is a scavenger receptor involved in lipid uptake and inflammation. Recently, non-cell-bound CD36 (sCD36) was identified in plasma and suggested to be a marker of lipid accumulation in the vessel wall. Marine n-3 polyunsaturated fatty acids (PUFA) may have cardioprotective effects. This study evaluated the effect of marine n-3 PUFA on sCD36 levels in overweight subjects. Fifty overweight subjects were randomized to 1.1 g of n-3 PUFA or 2 g of olive oil daily for six weeks. Neutrophils were isolated at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Omega-3 fatty acids have been shown to be incorporated into phospholipids in the cell membrane of neutrophils at the expense of the omega-6 fatty acids linoleic and arachidonic acid [13,60]. Once the omega-3 fatty acids have been incorporated into the phospholipids, they can be metabolized by neutrophils into prostaglandins, leukotrienes, thromboxanes, maresins, protectins, and resolvins [10,61,62].…”
Section: Effects Of Omega-3 Fatty Acids On Neutrophil Functionmentioning
confidence: 99%
“…Omega-3 fatty acids have been shown to be incorporated into phospholipids in the cell membrane of neutrophils at the expense of the omega-6 fatty acids linoleic and arachidonic acid [13,60]. Once the omega-3 fatty acids have been incorporated into the phospholipids, they can be metabolized by neutrophils into prostaglandins, leukotrienes, thromboxanes, maresins, protectins, and resolvins [10,61,62].…”
Section: Effects Of Omega-3 Fatty Acids On Neutrophil Functionmentioning
confidence: 99%
“…Most of the studies demonstrate that these fatty acids present important anti-inflammatory actions, which have been associated with different mechanisms including: alteration of cell membrane phospholipid fatty acid ͳͶ composition and consequentely change in the production of eicosanoids, disruption of lipid rafts and inhibition of transcription factors reducing the expression of proinflammatory genes(Calder, 2012; Martins de Lima et al, 2007).Incorporation of n-3 fatty acids in neutrophil membrane has been demonstrated by several groups in different conditions. In this context, low-dose of marine oil (1.1 g/day) ingestion, during 6 weeks, elevated the incorporation of n-3 fatty acids and reduced the percentage of arachidonic acid on neutrophil membranes(Veno et al, 2013).Sorensen et al (2014) demonstrated that ingestion of EPA (2.0 g/day) plus DHA (1.0 g/day) during 7 days increases by more than 3 fold the percentage of EPA and by 22% the incorporation of DHA in neutrophil membranes.…”
mentioning
confidence: 99%